PANCASILA SEBAGAI PEDOMAN HIDUP GENERASI MUDA BANGSA INDONESIA DI ERA MODERN - Ambarita, Vincent Prince Eden (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila, as the foundation of the state and the Indonesian nation's way of life, plays a crucial role in shaping the character and identity of the younger generation, particularly in the modern era marked by technological advances, globalization, and shifts in cultural values. This research aims to analyze the relevance and implementation of Pancasila values ​​in the lives of Indonesia's young generation amidst the challenges of the times. The method used was qualitative, using a literature study approach and social observation. The results of the study indicate that although globalization has significantly influenced the lifestyles and mindsets of the younger generation, Pancasila values ​​such as mutual cooperation, tolerance, justice, and patriotism remain relevant and can serve as guidelines in facing various social, economic, and cultural challenges. Therefore, strengthening Pancasila education and internalizing its values ​​creatively and contextually is crucial for maintaining the nation's identity and integrity in the future.